Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1469540518764238
|View full text |Cite
|
Sign up to set email alerts
|

Self-sewn identity: How female home sewers use garment sewing to control self-presentation

Abstract: Garment sewing was once a necessity for women to present themselves and their families in a socially acceptable manner. Despite societal and economics changes, as well as, an abundance of readily available cheap clothing, there is a resurging interest in personal garment sewing by women. This qualitative study explored the control gained by women who sew their own clothing finding that among the women interviewed personal garment sewing allowed them control over their clothing’s style, fit, and quality, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These consumers (retro sewers) actively rework and transform symbolic meanings found in both new and vintage material goods (patterns, fabrics, and notions) to further their retro identity and lifestyle goals. Building upon the work of Martindale and McKinney (2018), we find that retro sewers desires for a counterculture identity and lifestyle are enabled by their sewing skills. Rather than depending on existing marketplace clothing offerings, they can create the clothes to achieve the look that matches their desired identity and lifestyle.…”
Section: Influence Of Nostalgia On Retro Sewing Choices and Behaviors...mentioning
confidence: 91%
See 2 more Smart Citations
“…These consumers (retro sewers) actively rework and transform symbolic meanings found in both new and vintage material goods (patterns, fabrics, and notions) to further their retro identity and lifestyle goals. Building upon the work of Martindale and McKinney (2018), we find that retro sewers desires for a counterculture identity and lifestyle are enabled by their sewing skills. Rather than depending on existing marketplace clothing offerings, they can create the clothes to achieve the look that matches their desired identity and lifestyle.…”
Section: Influence Of Nostalgia On Retro Sewing Choices and Behaviors...mentioning
confidence: 91%
“…Retro sewers use marketer-produced fabrics, sewing patterns, and related items to create clothing that either replicates or is inspired by past fashions (typically 1920s through 1980s), to be worn for everyday use. Martindale and McKinney (2018) found that women who sew eschew typical retail-based consumption choices and behaviors. They sew to control their visual identity, including clothing style, fit, and quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Home sewers choose to sew their own clothing as a means of self-empowerment to control their appearance as well as a creative outlet (Martindale & McKinney, 2018). Retro sewers, who sew their own versions of historic styles to wear as part of their everyday lives, represent a unique intersection between the vintage clothing market and the home sewing market.…”
mentioning
confidence: 99%